Penerapan Sifat Amanah Pada Komisaris Independen Dan Komite Audit Dalam Mewujudkan Good Corporate Governance - Sari, Elin Nurlina; Aini, Nur; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
The role of Independent Commissioners and Audit Committees in carrying out their duties and authorities must comply with the professional code of ethics, in the implementation of Good Corporate Governance, the role of independent commissioners and audit committees that have a trustful nature is required. This paper tries to provide a fresh perspective by incorporating religious elements or religious values, especially Islam, namely trustworthiness. This characteristic will be used as a model to optimize the professional norms of independent commissioners and audit committees in implementing corporate governance. The methodology used in this article uses a literature review to draw conclusions from existing data sources and details the importance of emulating the nature of the Trust in the roles and responsibilities of independent commissioners and audit committees. This article explains the relationship between trustworthiness and optimizing the implementation of good corporate governance. The conclusion drawn is that the nature of trust must be applied to play its role in achieving good corporate governance. Because by applying trustworthiness to the principles of professional behavior, people will understand the applicable regulations and not take actions that tend to damage their professional reputation and tend to be honest and thorough in carrying out the tasks assigned to them.